The Effect of Contaminant on Xylene Separation by Zeolite Adsorption - S.M. Yih; H.C. Hsiao (Adsorption Science & Technology, 1988)
Possible contaminants arising from the oxidation of xylene isomers are detrimental to industrial adsorptive xylene separation processes since they lower the selectivity and recovery of p-xylene. A model compound, acetophenone, has been used to simulate the contaminant and it has been shown via pulse tests to adsorb strongly on to a K-BaY zeolite, thereby lowering the selectivity of p-xylene. Although the liquid desorbent PDEB (p-diethylbenzene) was not effective in removing the adsorbed acetophenone, nitrogen at 400°C and 1 atm was effective both in removing the adsorbed acetophenone and regenerating the adsorbent. Measurements of the adsorption capacity of acetophenone have shown that Molecular Sieve 13 X and K-BaY zeolites are both good adsorbents for acetophenone.